2006
DOI: 10.1007/s10661-005-9003-x
|View full text |Cite
|
Sign up to set email alerts
|

Distribution Of Volatile Organic Compounds In Ambient Air Of Kaohsiung, Taiwan

Abstract: Automobile emissions have created a major hydrocarbon pollution problem in the ambient air of Taiwan. The aim of this study was to determine the volatile organic compounds (VOCs) in the ambient air of Kaohsiung, Taiwan. The spatial distribution, temporal variation, and correlations of VOCs at three study sites, selected based on traffic densities and distances from a freeway, were discussed. Sixty-four hydrocarbons were identified in the ambient air. Among all of the VOC species, acetone, aromatic and aliphati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 19 publications
0
4
0
Order By: Relevance
“…Benzene is a marker of vehicle exhaust (Hong et al, 2006) and toluene is an important component emitted from evaporation of solvents used in ink, paint and light motor vehicles (Zalel and Broday, 2008). In Li et al (2009), the B/T ratios were 1.9 ± 0.62 and higher B/T ratios (N1) were thought to be associated with biomass burning, coal burning and industrial emissions.…”
Section: Diagnostic Ratios Of the Four Types Of Coal-fired Source Promentioning
confidence: 99%
“…Benzene is a marker of vehicle exhaust (Hong et al, 2006) and toluene is an important component emitted from evaporation of solvents used in ink, paint and light motor vehicles (Zalel and Broday, 2008). In Li et al (2009), the B/T ratios were 1.9 ± 0.62 and higher B/T ratios (N1) were thought to be associated with biomass burning, coal burning and industrial emissions.…”
Section: Diagnostic Ratios Of the Four Types Of Coal-fired Source Promentioning
confidence: 99%
“…Several authors have reported that VOC emissions reach their maximum values in winter and the minimum in spring or summertime [17][18][19][20][21] although some others have not observed these variations according to the season 22 or reported the highest concentrations in summertime. 23 Baldasano et al 24 found that the emissions in the urban area of Martorell (NE Spain) followed the common pattern with higher concentrations in winter and lower in summer; however in the suburban area of the same city this difference was not so clear since the averaged summer and winter emissions were equivalent.…”
Section: Seasonal Btex Profilesmentioning
confidence: 99%
“…As one good example of such applications, the T/B ratios can be examined as a function of distance to the road (Gelencsr et al, 1997). In this study, the median value of T/B ratios at 4 sites (5.9-9.4) were much higher than those reported in many other urban areas like Rome, Changchum (China), Kaohsiung (Taiwan), and Thessaloniki (Greece) (Hong et al, 2006;Kelessis et al, 2006;Lai et al, 2004;Liu et al, 2000;Brocco et al, 1997). However, these values are rather comparable to those in most of Asian countries such as: Bangkok (10.22), Hong Kong (7.74), and Osaka (7.19) Gee and Sollars, 1998;Tsujino and Kuwata, 1993).…”
Section: Distribution Characteristics Of Vocmentioning
confidence: 64%
“…Benzene, well-known as tracer for automobile exhaust, showed a good correlation (p⁄0.01, p⁄ 0.05) with other VOCs and criteria pollutants at JR, GJ, and GS. However, no such correlation was evident at YJ (Hoque et al, 2008;Hong et al, 2006;Rudd, 1995;Chan et al, 1991). The lack of correlation between benzene and other VOC species in the YJ site suggests that the sources of VOCs in YJ are more complicated in Seoul relative to the other study areas.…”
Section: The Factors Affecting Voc Distributionsmentioning
confidence: 99%